Biogas Stoves Reduce Firewood Use, Household Air Pollution, and Hospital Visits in Odisha, India - Lewis, Jessica J; Hollingsworth, John W; Chartier, Ryan T; Cooper, Ellen M; Foster, William Michael; Gomes, Genna L; Kussin, Peter S; MacInnis, John J; Padhi, Bijaya K; Panigrahi, Pinaki; Rodes, Charles E; Ryde, Ian T; et al. (Environmental science & technology, 2017)
Traditional cooking using biomass is associated with ill health, local environmental degradation, and regional climate change. Clean stoves (liquefied petroleum gas (LPG), biogas, and electric) are heralded as a solution, but few studies have demonstrated their environmental health benefits in field settings. We analyzed the impact of mainly biogas (as well as electric and LPG) stove use on social, environmental, and health outcomes in two districts in Odisha, India, where the Indian government has promoted household biogas. We established a cross-sectional observational cohort of 105 households that use either traditional mud stoves or improved cookstoves (ICS). Our multidisciplinary team conducted surveys, environmental air sampling, fuel weighing, and health measurements. We examined associations between traditional or improved stove use and primary outcomes, stratifying households by proximity to major industrial plants. ICS use was associated with 91% reduced use of firewood (p < 0.01), substantial time savings for primary cooks, a 72% reduction in PM , a 78% reduction in PAH levels, and significant reductions in water-soluble organic carbon and nitrogen (p < 0.01) in household air samples. ICS use was associated with reduced time in the hospital with acute respiratory infection and reduced diastolic blood pressure but not with other health measurements. We find many significant gains from promoting rural biogas stoves in a context in which traditional stove use persists, although pollution levels in ICS households still remained above WHO guidelines.